2011
DOI: 10.1182/blood-2010-12-325589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thalidomide and lenalidomide as therapy for myelofibrosis

Abstract: With the use of the International Working Group for Myelofibrosis Treatment andResearch consensus criteria, we reassessed the efficacy of thalidomide and lenalidomide in 125 patients with myelofibrosis treated in 3 consecutive phase 2 trials: 44 received single-agent thalidomide, 41 single-agent lenalidomide, and 40 a combination of lenalidomide plus prednisone. The thalidomide group included significantly more untreated patients and patients with performance status of 2. The Lenalidomide-based therapy produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 10 publications
1
48
0
1
Order By: Relevance
“…However, in a prospective multi-center study [8], the combination of lenalidomide and prednisone resulted in only 19% anemia response and 23% overall response. Regardless, the use of thalidomide or lenalidomide in MF is limited by the respective occurrence of peripheral neuropathy [12] and moderate to severe myelosuppression [8], in the majority of treated patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a prospective multi-center study [8], the combination of lenalidomide and prednisone resulted in only 19% anemia response and 23% overall response. Regardless, the use of thalidomide or lenalidomide in MF is limited by the respective occurrence of peripheral neuropathy [12] and moderate to severe myelosuppression [8], in the majority of treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Lenalidomide (5-10 mg/day), with or without prednisone, also alleviated anemia in a similar proportion of patients with MF [3,8,9], and was most useful in the presence of del(5q) [10]. Two recent studies reassessed treatment response using the International Working Group for Myeloproliferative Neoplasms Research and Treatment (IWG-MRT) criteria [11]; one study reported up to 38% response rate for lenalidomide plus prednisone therapy [12] whereas the other study reported 28% response rate for thalidomide-based therapy [13]. However, in a prospective multi-center study [8], the combination of lenalidomide and prednisone resulted in only 19% anemia response and 23% overall response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myelosuppression was the main toxicity, with 88% of the patients having grade 3 or higher hematologic toxicity in one trial [37]. With the use of the International Working GroupMyelofibrosis Research and Treatment (IWG-MRT) criteria [38], the efficacy of lenalidomide was reassessed in 81 patients treated in phase 2 trials at the MD Anderson Cancer Center [39]. The results were compared with those of patients who received thalidomide as a single agent.…”
Section: New Therapies For Anemiamentioning
confidence: 99%
“…However, recent studies suggest that it may be utilised in older individuals as well (14,15). Other therapeutic modalities (e.g., thalidomide, hydroxyurea, corticosteroids, anagrelide, androgens, splenectomy or spleen irradiation, transfusions, pirfenidone and suramin) are only palliative and do not provide a substantial improvement in survival rates (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%